2010
DOI: 10.1007/s00234-009-0645-1
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral atrophy as outcome measure in short-term phase 2 clinical trials in multiple sclerosis

Abstract: IntroductionCerebral atrophy is a compound measure of the neurodegenerative component of multiple sclerosis (MS) and a conceivable outcome measure for clinical trials monitoring the effect of neuroprotective agents. In this study, we evaluate the rate of cerebral atrophy in a 6-month period, investigate the predictive and explanatory value of other magnetic resonance imaging (MRI) measures in relation to cerebral atrophy, and determine sample sizes for future short-term clinical trials using cerebral atrophy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 21 publications
3
18
0
Order By: Relevance
“…This appears to be true in both relapsing–remitting multiple sclerosis (RRMS) and benign MS, suggesting a silent progression of cognitive impairment independent of MS clinical course (Gonzalez‐Rosa et al., 2006). Indeed, while MS is characterized by WM lesions, GM atrophy is considered to be a relevant biomarker of permanent disability in MS (Bermel & Bakshi, 2006; van den Elskamp et al., 2010; Fisher et al., 2002). In fact, GM atrophy has been found to be associated with changes in all cognitive domains in MS (Morgen et al., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This appears to be true in both relapsing–remitting multiple sclerosis (RRMS) and benign MS, suggesting a silent progression of cognitive impairment independent of MS clinical course (Gonzalez‐Rosa et al., 2006). Indeed, while MS is characterized by WM lesions, GM atrophy is considered to be a relevant biomarker of permanent disability in MS (Bermel & Bakshi, 2006; van den Elskamp et al., 2010; Fisher et al., 2002). In fact, GM atrophy has been found to be associated with changes in all cognitive domains in MS (Morgen et al., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative magnetic resonance imaging (MRI) studies indicate that gray matter atrophy occurs even in the earliest stages of disease (Calabrese et al, 2007; Dalton et al, 2004; De Stefano et al, 2003) and is more closely related to physical disability and cognitive impairment than either T2 or T1 white matter lesion volumes (Amato et al, 2004; Chard et al, 2002; Sailer et al, 2003; Sanfilipo et al, 2006). Indeed, it is now considered to be one of the most relevant markers of permanent disability in MS (Bermel and Bakshi, 2006; Fisher et al, 2002; van den Elskamp et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…The recent research shows that the axonal loss is one of the main reasons for the atrophy, which is associated with the number of T2 lesions. Also, the rate of cerebral atrophy is a detectable outcome measure in short term clinical trials in RRMS and applicable in terms of study power while a potent drug is applied [6]. Quarantelli et al [7], Pagani et al [8], Horakova et al [9], Fisher et al [10], and Fisniku et al [11] have confirmed that tissue loss in GM compartment is greater than the WM.…”
Section: Introductionmentioning
confidence: 88%